What role does technology play in the operation of terrorists and what role can it play in the future? - Kurowski, Bartosz (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The aim of the article is to emphasize the importance of modern technology in the activities of the Islamic State, which, as one of the first terrorist groups in the world, recognized the great potential of the media as ready-made tools to spread propaganda or arouse fear among society. The increasingly emerging phenomenon of electronic jihad – recruiting new fighters using the Internet – or spreading disinformation in terrorist-controlled areas by means of newspapers and propaganda leaflets, are only a small outline of the entire jihadist propaganda machine. Particular priority has therefore been placed on indicating the media structure, propaganda products, and the goals of the Islamic State, which seem to evolve over the years along with the changing environment and progressing globalization. Therefore, modern terrorism, more and more often referred to as cyberterrorism, is simultaneously becoming a completely new threat and challenge for the security apparatus.